Vāznahʻnāmah-ʻi basāmadī-i Pisālah-ʻi jūdīyah-ʻi ibn-i Sīnā - Ḥasanpūr, Maḥmūd (Farhangistān-i Zabān-i Īrān, 1975)
Glossary and index to Risālah-ʻi jūdīyah, a treatise on Arabic medicine, by Avicenna, 980-1037.